Pengaruh Self-Efficacy sebagai Upaya dalam Menangani Stres Akademik pada Siswa Sekolah Dasar - Indah Amalina Husnah; Khairunnisa Khairunnisa; Luthfi Syahel; Mahirah Naifa Mardiah; Salina Octaviani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
Academic stress has become a common problem that needs to be considered carefully. Self-efficacy is a person's belief in understanding their ability to complete academic tasks based on self-confidence about the achievements obtained. Students have relevant corrections between learning outcomes and the academic stress they have. The purpose of this study was to determine the effect of self-efficacy as an effort to deal with academic stress in elementary school students. This study uses a literature review method from previous studies with sources used from Google Scholar and the selected journal years have been published in 2021-2025. The results of this study indicate that self-efficacy has an influence on academic stress in elementary school students and provides insight for educators into optimal psychological and academic development of children.